Project: Information Oasis - Katherine Clemens; Emalee Craft; Jennifer Duvernay; Sheila Hofstetter; Linda Shackle (Issues in Science and Technology Librarianship)
The article discusses a welcome table outside the library entrance as a way to increase library visibility and have more personal contact with students. Table is called the "Information Oasis."